Impact of Personal Selling and Sales Promotion Strategy on Market Performance of Selected Manufacturing Companies in Lagos State, Nigeria - Ibeh; J.I; J.O and Nwajimeje J, Nnabuko (British Journal of Marketing Studies, 2022)
Understanding how personal selling and sales promotional strategy impact on the market performance after high capital investments is crucial to the contribution of the food and beverage companies in national economic growth; however, there is dearth of information on this subject matter. The main objective of the study is to examine the effect of personal selling and sales promotion strategy on the market performance of selected manufacturing companies in Lagos State Nigeria. specifically, the study determine the effect of sales promotion on the market performance of  manufacturing companies in Lagos Nigeria and determine the effect of personal selling on the market performance of these manufacturing companies in Lagos Nigeria. Econometric technique involving descriptive research, correlation coefficient and multiple regressions was used for the data analysis. A population and sample of 24 product promotional related managers were drawn through a census sampling technique. Two research instruments – Annual Report/Financial Statement and Questionnaire were used for data collection. The result of the study indicates that there is significant predictive impact of sales promotional strategy on the market performance and that there is significant contribution of the promotional tool on the profit margin level of all six companies. the stud therefore conclude that personal selling and sales promotion strategy have positive and significant impact on market performance of selected manufacturing companies in Lagos, Nigeria.  Amongst the recommendations is that staff saddle with the implementation of personal selling and sales promotional strategy should devote time and resources into it since it largely influence profitability of the companies.Citation: Ibeh, J.I, Nnabuko J.O and Nwajimeje J.(2022) Impact of Personal Selling and Sales Promotion Strategy on Market Performance of Selected Manufacturing Companies in Lagos State, Nigeria; British Journal of Marketing Studies, Vol. 10, Issue 5, pp.,54-74